2020
DOI: 10.3892/mco.2020.2140
|View full text |Cite
|
Sign up to set email alerts
|

HER2‑positive breast cancer that resists therapeutic drugs and ionizing radiation releases sphingomyelin‑based molecules to circulating blood serum

Abstract: Breast cancer is the second most common cancer in the world based on incidence, reaching more than 2 million new cases in 2018, while continuing to increase. Invasive ductal carcinoma is the most common type of this cancer, making up approximately 70-80% of all breast cancer diagnoses. In particular, the type of breast cancer overexpressing human epidermal growth factor receptor 2 (HER2) has potential of strong proliferation, migration and invasion and early treatment is necessary. The authors identified and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Several lines of research documented the role of surface membrane SM in tumorigenesis. First, changes in sphingolipids levels were established for several tumor cells and cell lines [ 52 57 ]. More specifically, level of SM in the outer leaflet of cell plasma membrane was reported to be significantly elevated in highly metastatic human prostatic adenocarcinoma cell lines compared to the lower metastatic variant [ 52 ].…”
Section: Tumor Immune Evasionmentioning
confidence: 99%
“…Several lines of research documented the role of surface membrane SM in tumorigenesis. First, changes in sphingolipids levels were established for several tumor cells and cell lines [ 52 57 ]. More specifically, level of SM in the outer leaflet of cell plasma membrane was reported to be significantly elevated in highly metastatic human prostatic adenocarcinoma cell lines compared to the lower metastatic variant [ 52 ].…”
Section: Tumor Immune Evasionmentioning
confidence: 99%
“…Evaluating whether SL plasma levels can be predictive determinants for the SL status in tumors was the main objective of the metabolomic approach applied in two studies. Indeed, Miolo et al [122] identified circulating spermidine and tryptophan as potential markers associated with the complete pathological response to trastuzumab-paclitaxel neoadjuvant therapy in HER2+ BC.More interestingly, Monzen S. et al [123] recently reported not only a parallel expression intensity of HER2 and nSMase2, possibly connected to cell communication by extracellular vesicles (EVs) [124], but also that the serum concentration of four SM species [SM 24:1, SM C26:0, hydroxySM C16:1 and hydroxySM C24:1] were inversely related to the accumulation of nSMase2 in HER2+ cancer tissues from a patient who exhibited complete therapeutic resistance to monoclonal-anti-HER2 antibody therapy, chemotherapy and radiotherapy after mastectomy. Clearly, further and detailed analyses are needed on a larger number of patients.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…114 Numerous articles have documented the role of excessive content of surface membrane sphingomyelin and down-regulation of the membrane-associated neutral sphingomyelinase in tumor immune evasion, initiation, growth and drug resistance of hepatic, breast, ovarian, brain, and bone cancer growth and metastasis. 4,[115][116][117][118][119][120][121][122] In that context, it is timely to recall that potent activators of neutral sphingomyelinases, notably long-chain polyunsaturated fatty acids such as arachidonic acid, are increasingly documented as safe and efficacious in prevention and therapy of clinicallydetected tumors. 4,[123][124][125]…”
Section: Future Directionsmentioning
confidence: 99%